Invasive mucinous carcinoma of the breast and response patterns after neoadjuvant chemotherapy (NAC). Issue 6 (14th February 2018) - Didonato, Rosemarie; Shapiro, Nella; Koenigsberg, Tova; D'Alfonso, Timothy; Jaffer, Shabnam; Fineberg, Susan
Abstract : Aims: Neoadjuvant chemotherapy (NAC) is often used to treat localised invasive breast cancer. Invasive mucinous carcinoma (IMC) is considered to be an indolent form of invasive breast cancer, and is rarely treated with NAC. We report the largest series of IMCs treated with NAC, and report a characteristic, but not well recognised, pattern of pathological response. Methods and results: Our series included seven patients with IMC treated with NAC. Three patients presented with locally advanced disease, three patients had tumours that were HER‐2/ neu ‐positive, and four patients had tumours with admixed mucinous and micropapillary features. Clinical and imaging assessment of response showed persistent and, in some cases, progressive disease, despite evidence of significant pathological response in these cases. Pathological assessment after NAC demonstrated marked reduction in tumour cellularity, but persistent space‐occupying mucin pools, showing acellular mucin in one case, <1% tumour cellularity in three cases, and 5–10% cellularity in three cases in both the treated breast and axillary lymph nodes. Conclusions: Persistent mass‐forming low‐cellular or acellular mucin pools can result in discordant clinical, imaging and pathological findings in IMC treated with NAC.